Politeness in the Mamongkot Traditional Ceremony of the Bayu House of the Simalungun Batak Ethnic Group: A Normative Study: - Flansius Tampubolon; Lastiur Sinaga; Anggun Yuni Sarah Sijabat; Roma Hotni Uhur Purba; Ridho Wahyu C. Silaban; Jonathan Halomoan Marpaung (Raja Zulkarnain Education Foundation, 2026)
This study examines the values of politeness and courtesy in the Mamongkot Rumah Bayu traditional ceremony of the Batak Simalungun community in North Sumatra. This ceremony is held as an expression of gratitude and a request for blessings from God when someone moves into a new house. This tradition not only has spiritual significance but is also imbued with social and moral norms that guide community behavior. This study used a qualitative approach with a normative-descriptive method, conducted through observation, interviews with traditional leaders, and literature review to understand the symbolic meaning and function of traditional values in social life. The results show that politeness is reflected in polite speech, modest dress, and respect for traditional elders. Politeness is seen as a behavioral guideline that maintains social harmony and demonstrates respect for others. Meanwhile, politeness is evident in the form of mutual cooperation, caring, and the provision of food or ulos (traditional clothing) to guests as a symbol of love and blessings. These values not only serve to strengthen social relationships but also serve as a form of spiritual devotion to God and ancestors. The Mamongkot Rumah Bayu ceremony plays a crucial role as a character education tool, instilling values of respect, empathy, and solidarity in the younger generation. Amidst the tide of modernization, the values of politeness and courtesy remain relevant as a moral foundation for building an ethical, harmonious, and civilized society.